2006
DOI: 10.1183/09031936.06.00126004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of initial antibiotic choice on mortality from pneumococcal pneumonia

Abstract: To determine the impact of initial antimicrobial choice on 30-day mortality rate in patients with community-acquired pneumonia due to Streptococcus pneumoniae (CAP-SP), a prospective, observational study was conducted in 35 Spanish hospitals. A total of 638 patients with CAP-SP were identified. Antimicrobials were chosen by the attending physician. Patients were grouped into the following categories: b-lactam monotherapy (n5251), macrolide monotherapy (n537), b-lactam plus macrolide (n5198), levofloxacin alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(40 citation statements)
references
References 43 publications
1
33
2
4
Order By: Relevance
“…Taking into account the relationship between IL-6 and poor prognosis for PP, the modulation of the expression of this cytokine may be a key point for improving patient outcomes. Whether combination therapy can improve outcomes in patients with CAP is a controversial issue [21][22][23][24][25][26]. Moreover, most studies have used the combination of -lactam plus macrolide, not -lactam plus fluoroquinolone.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account the relationship between IL-6 and poor prognosis for PP, the modulation of the expression of this cytokine may be a key point for improving patient outcomes. Whether combination therapy can improve outcomes in patients with CAP is a controversial issue [21][22][23][24][25][26]. Moreover, most studies have used the combination of -lactam plus macrolide, not -lactam plus fluoroquinolone.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies showed no effect [25][26][27][28]. Some features of these studies are described in table 4; most studies were retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…In several retrospective or nonrandomized prospective clinical studies, a survival benefit has been shown in patients with pneumococcal CAP treated with a combination of b-lactam antibiotics and macrolides compared with those treated with b-lactam monotherapy [61][62][63][64][65]. However, two large prospective cohort studies showed no difference between these two regimens [66,67]. In a retrospective study in patients with severe sepsis owing to pneumonia caused by any microorganism, macrolide use was associated with decreased mortality, even in patients with macrolideresistant pathogens [68].…”
Section: Macrolide Antibioticsmentioning
confidence: 99%